ECOLOGY AND ENVIRONMENT, INTERACTIONS BETWEEN ORGANISMS AND THEIR ENVIRONMENT (International Bulletin of Medical Sciences and Clinical Research, 2024)
The field of ecology and environment encompasses the study of the interactions between organisms and their environment, as well as the examination of environmental processes, conservation, and sustainable practices. This article provides an overview of key concepts and topics within this field, including biodiversity, ecosystems, environmental impact assessment, sustainable development, and ecological economics. It explores the importance of understanding ecological principles, addressing environmental challenges, and promoting responsible behavior towards the environment. The article emphasizes the need for interdisciplinary approaches, collaboration, and effective environmental governance to achieve ecological sustainability.